Design of a miniature pump - Tan, Tat Cheng. (2013)
Macro size pumps do have their limitations which constricts the number of applications it could serve. On the other hand, the miniature pump opens up a new area of applications as it brought about mobility, precision flow rate, convenience and etc. Design and development of the miniature pump is necessary in serving these applications, however, miniaturization is a very challenging process.